STRATEGIES OF MANIPULATIVE RHETORIC IN THE ENGLISH-LANGUAGE BUSINESS MEDIA DISCOURSE - Elena N. Malyuga; Elena I. Madinyan (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
The aim of the study is to identify manipulative strategies implemented through the use of collocations, clichés, idioms, and set phrases in the English-language business media discourse. A quantitative analysis of samples collected from publications in “The Economist” was conducted. The research hypothesis proposes that manipulative strategies in the English-language business discourse are realized through the deliberate choice of collocations, clichés, idioms, and set phrases, which serve as tools for shaping public opinion. The study identified five manipulative strategies. It was established that manipulation through imagery-based expressions is the most frequently employed strategy, while evaluative assessments of factual content and manipulation by criticism are less frequent. The least utilized strategies are manipulation through antithesis and generalization, manipulation via vague or euphemistic language constructions. The research confirmed that collocations, clichés, idioms, and set phrases are extensively used in the English-language business media discourse to implement manipulative strategies, and several strategies may be joined within a single utterance. The findings may have scientific implications, particularly for scholars and professionals in media and business communication.